The influence of the STEAM-based PjBL model in IPAS learning on critical thinking skills - Eka Lita Sofiani; Kusmadjid Abdullah (Inovasi Kurikulum, 2025)
This research is motivated by the low critical thinking skills of students in science learning. This study aims to investigate the impact of the project-based learning (PjBL) model, grounded in the Science, Technology, Engineering, Arts, and Mathematics (STEAM) framework, on the critical thinking skills of elementary school students. The research method uses a quantitative approach with a one-group pretest-posttest pre-experimental design. The participants of the study are fifth-grade students at an elementary school in East Jakarta. The instrument used consists of critical thinking questions that are written based on specified criteria. The results of the study indicate a significant improvement in critical thinking skills after using the STEAM-based PjBL approach in science learning, particularly in the topic of electrical energy. This is evidenced by the students' ability to analyze problems, devise solutions, and assess their effectiveness. Thus, it can be concluded that the PjBL learning model based on STEAM has a positive influence on the development of students' critical thinking skills. This paradigm provides a more dynamic, substantial, and contextual learning experience for students.   Abstrak Penelitian ini dilatarbelakangi oleh rendahnya kemampuan berpikir kritis peserta didik dalam pembelajaran IPA. Penelitian ini bertujuan untuk mengkaji pengaruh model pembelajaran berbasis proyek (PjBL) berbasis kerangka Science, Technology, Engineering, Arts, dan Mathematics (STEAM) terhadap keterampilan berpikir kritis peserta didik sekolah dasar. Metode penelitian ini menggunakan pendekatan kuantitatif dengan rancangan one-group pretest-posttest pre-experimental design. Partisipan penelitian adalah peserta didik kelas V SD di salah satu sekolah dasar di Jakarta Timur. Instrumen yang digunakan berupa soal-soal berpikir kritis yang ditulis berdasarkan kriteria yang ditentukan. Hasil penelitian menunjukkan adanya peningkatan keterampilan berpikir kritis yang signifikan setelah menggunakan pendekatan PjBL berbasis STEAM pada pembelajaran IPAS khususnya pada materi energi listrik. Hal ini dibuktikan dengan kemampuan peserta didik dalam menganalisis permasalahan serta membuat solusi dan mengevaluasinya. Dengan demikian, dapat disimpulkan bahwa model pembelajaran PjBL berbasis STEAM memberikan pengaruh yang positif terhadap perkembangan keterampilan berpikir kritis peserta didik. Paradigma ini memberikan pengalaman belajar yang lebih dinamis, substansial, dan kontekstual bagi peserta didik. Kata Kunci: berpikir kritis; project-based learning; STEAM